2017
DOI: 10.1007/s41252-017-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Markers of Challenging Behavior Among Children with Disabilities

Abstract: Children with disabilities are more likely to engage in some form of challenging behavior. The present study sought to investigate the prevalence of challenging behaviors, such as aggressive/destructive or stereotypic behavior, and identify those personal and contextual risk markers associated with the occurrence of challenging behaviors. A total of 205 children with intellectual disability enrolled in a special education school participated in this study. Fifteen professionals participated in this study and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Consistent with previous research, the prevalence of problem behavior was depending on the nature of the sample. For example, a high percentage of children with autism presented at least one type of problem behavior (Simó-Pinatella et al 2017). Although previous studies have reported the problem behavior prevalence in different ways (e.g., providing the percentage for each item, e.g., Lecavalier 2006), when looking at the type of the behavior exhibited, some similarities can be found.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with previous research, the prevalence of problem behavior was depending on the nature of the sample. For example, a high percentage of children with autism presented at least one type of problem behavior (Simó-Pinatella et al 2017). Although previous studies have reported the problem behavior prevalence in different ways (e.g., providing the percentage for each item, e.g., Lecavalier 2006), when looking at the type of the behavior exhibited, some similarities can be found.…”
Section: Discussionmentioning
confidence: 93%
“…The topographies of SIB are a broad class of self-directed behaviors that cause physical harm to the body (Shawler et al, 2019; Tate & Baroff, 1966), target the full spectrum of body sites (Steenfeldt-Kristensen et al, 2020), and occur with varying intensities ranging from producing discomfort, to causing tissue damage, and potentially resulting in permanent injury or disfigurement. Prevalence estimates of SIB in individuals with IDD are variable (e.g., 5.3%, Ruddick et al, 2015; 47.2%, Simó-Pinatella et al, 2017) but consistently elevated in autistic people, including 52.3% of children (Duerden et al, 2012) and 42% across the lifespan (Steenfeldt-Kristensen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Functional analysis is especially important for neurodivergent populations and those with developmental delays (Kim, 2023). There is a higher prevalence of challenging behaviors in populations with autism and/or intellectual disabilities than in those without these diagnoses (Didden et al, 2012;Jang et al, 2011;Lundqvist, 2013;Mazurek et al, 2013;McTiernan et al, 2011;Murphy et al, 2009;Nicholls et al, 2020Nicholls et al, , 2023Simó-Pinatella et al, 2017, 2019. Challenging behaviors, such as aggression, selfharm, and destruction of property, are more likely to occur in people diagnosed with autism than in those with intellectual disabilities (Kim, 2023).…”
Section: Introductionmentioning
confidence: 99%